2008
DOI: 10.1016/j.neuroscience.2008.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Aged-related loss of temporal processing: Altered responses to amplitude modulated tones in rat dorsal cochlear nucleus

Abstract: Loss of temporal processing is characteristic of age-related loss of speech understanding observed in the elderly. Inhibitory glycinergic circuits provide input onto dorsal cochlear nucleus (DCN) projection neurons which likely serve to modulate excitatory responses to time-varying complex acoustic signals. The present study sought to test the hypothesis that age-related loss of inhibition would compromise the ability of output neurons to encode sinusoidally amplitude modulated (SAM) tones. Extracellular recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 84 publications
0
44
0
Order By: Relevance
“…In an animal model, Schatteman et al [2008] suggest that the age-related loss of temporal resolution skill is not simply the result of an increase in the firing rate, which could decrease synchrony at the best modulation frequency. The decreased synchrony is also related to a reduction in timed inhibitory postsynaptic currents, which could in turn be responsible for the loss of temporal coding.…”
Section: Discussionmentioning
confidence: 97%
“…In an animal model, Schatteman et al [2008] suggest that the age-related loss of temporal resolution skill is not simply the result of an increase in the firing rate, which could decrease synchrony at the best modulation frequency. The decreased synchrony is also related to a reduction in timed inhibitory postsynaptic currents, which could in turn be responsible for the loss of temporal coding.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in neural inhibition with aging have been established (Caspary et al, 2005 and age-related changes in GABA have been shown to affect temporal processing (Fukui et al, 2010;Schatteman et al, 2008). More specifically, changes in GABA and Fig.…”
Section: Age-related Changes In Dynamic Frequency Representationmentioning
confidence: 99%
“…Recently, Caspary and colleagues successfully recorded responses to SAM tones from FCs in young adult and old Fisher Brown Norway rats (Schatteman et al, 2008). Neural coding of SAM tones using three modulation depths (20%, 50% and 100%) were presented 30 dB above the neuron's best frequency (BF), and rate and synchronization MTFs were collected.…”
Section: Age-related Temporal Processing Deficits In the Cochlear Nucmentioning
confidence: 99%
“…Note the significant loss of BP units in the aged rats, especially for the 100% modulation depth carrier, with a concomitant increase in low-pass units. (adapted with permission fromSchatteman et al (2008).) Age-related decline in temporal coding of AM signals at all modulation depths plotted as a function of the unit's PSTH type, where B = buildup, PB = pauserbuildup and WC = wideband chopper.…”
mentioning
confidence: 99%
See 1 more Smart Citation